2018
DOI: 10.1080/09168451.2018.1431518
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of lncRNA ZFAS1 inhibits malignancies by blocking Wnt/β-catenin signaling in gastric cancer cells

Abstract: Gastric cancer is a common malignancy with high mortality. Long noncoding RNA (lncRNA) zinc finger antisense (ZFAS)1 is upregulated in gastric cancer specimens compared with the para-carcinoma tissues. The silencing of ZFAS1 inhibited the growth, proliferation, cell cycle progress, migration, invasion and epithelial-mesenchymal transition (EMT), and enhanced the sensitivity to cis-platinum or paclitaxel in SGC7901 cells, as evidenced by the expression changes of proliferating cell nuclear antigen, Cyclin D1, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…qRT-PCR results revealed that LncRNAZFAS1 was significantly up-regulated in NSCLC-related tissues and cells, compared with relative normal tissues and cells. Similar results were investigated in nasopharyngeal carcinoma, colorectal cancer (CRC) and gastric cancer (Thorenoor et al 2016;Fang et al 2017;Chen et al 2018;Xie et al 2018;Xu et al 2018). To indicate the relationship between the expression level of LncRNAZFAS1 and tumor stage and metastasis, we found that LncRNAZFAS1 was significantly overexpressed in stage III / IV and in metastatic NSCLC tissues, further indicating that elevated LncRNAZ-FAS1 was remarkably correlated with TNM stage and lymph node metastasis and may promote the progression and metastasis of NSCLC.…”
Section: Discussionsupporting
confidence: 75%
“…qRT-PCR results revealed that LncRNAZFAS1 was significantly up-regulated in NSCLC-related tissues and cells, compared with relative normal tissues and cells. Similar results were investigated in nasopharyngeal carcinoma, colorectal cancer (CRC) and gastric cancer (Thorenoor et al 2016;Fang et al 2017;Chen et al 2018;Xie et al 2018;Xu et al 2018). To indicate the relationship between the expression level of LncRNAZFAS1 and tumor stage and metastasis, we found that LncRNAZFAS1 was significantly overexpressed in stage III / IV and in metastatic NSCLC tissues, further indicating that elevated LncRNAZ-FAS1 was remarkably correlated with TNM stage and lymph node metastasis and may promote the progression and metastasis of NSCLC.…”
Section: Discussionsupporting
confidence: 75%
“…For instance, ZFAS1 was found to promote resistance to Adriamycin in T-cell acute lymphoblastic leukemia [45]. ZFAS1 knockdown led to significantly impaired resistance to cis-platinum or paclitaxel in gastric cancer [46]. Increased resistance to temozolomide in glioma [47].…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have indicated that lncRNAs serve important functions in the regulation of biological processes, including proliferation, cell survival and cell mobility (23). LncRNAs are widely involved in tumorigenesis (24) and a number of lncRNAs have been reported to regulate BC progression (25,26). Li et al (27) reported that lncRNA ANCR regulated EZH2 degradation and attenuated the invasion and metastasis of BC.…”
Section: Discussionmentioning
confidence: 99%